Implementation of Ring-Oscillators-Based Physical Unclonable Functions with Independent Bits in the Response. (12th April 2012) - Bernard, Florent; Fischer, Viktor; Costea, Crina; Fouquet, Robert
Abstract : The paper analyzes and proposes some enhancements of Ring-Oscillators-based Physical Unclonable Functions (PUFs). PUFs are used to extract a unique signature of an integrated circuit in order to authenticate a device and/or to generate a key. We show that designers of RO PUFs implemented in FPGAs need a precise control of placement and routing and an appropriate selection of ROs pairs to get independent bits in the PUF response. We provide a method to identify which comparisons are suitable when selecting pairs of ROs. Dealing with power consumption, we propose a simple improvement that reduces the consumption of the PUF published by Suh et al. in 2007 by up to 96.6%. Last but not least, we point out that ring oscillators significantly influence one another and can even be locked. This questions the reliability of the PUF and should be taken into account during the design.